HIGH-OXIDATION-STATE PENTAMETHYLCYCLOPENTADIENYL TUNGSTEN HYDRAZINE AND HYDRAZIDO COMPLEXES AND CLEAVAGE OF THE N-N BOND - SCHROCK, RR; GLASSMAN, TE; VALE, MG; KOL, M (Journal of the American Chemical Society, 1993)
[Cp*WMe3(eta2-NH2NH2)][OTf] (1a), which is prepared by adding hydrazine to Cp*WMe3(OTf), is a pseudooctahedral complex in which the N(1)-N(2) bond distance is 1.43(1) angstrom. Deprotonation of 1a is proposed to yield unobserved Cp*WMe3(NHNH2), which disproportionates to a mixture of 0.5 equiv of Cp*WMe3(eta1-NNH2), 0.5 equiv of Cp*WMe3(NH), and 0.5 equiv of ammonia. The proposed intermediates in the disproportionation reaction are Cp*WMe3(eta2-NNH2) and Cp*WMe3(eta2-NH2NH2). The instability of Cp*WMe3(eta2-NH2NH2) toward N-N bond cleavage is suggested by the reduction of [Cp*WMe3(eta2-NH2NH2)]+ to give a 1:1 mixture of Cp*WMe3(NH) and ammonia. Addition of 1,2-dimethylhydrazine to Cp*WMe3(OTf) in ether yields red crystalline [Cp*WMe3(eta2-NHMeNHMe)][OTf] (1b), which upon deprotonation yields a mixture of 0.5 equiv of Cp*Wme3(eta2-MeNNMe) and 0.5 equiv of Cp*Wme3(NMe) via (it is proposed) disproportionation of Cp*WMe3(NMeNHMe). Deprotonation of [Cp*WMe3(eta2-NMeNHMe)]+ yields Cp*WMe3(eta2-MeNNMe) quantitatively. An X-ray structure of Cp*WMe3(eta2-MeNNMe) revealed that the dimethyldiazene ligand is bound to the metal in the expected eta2 manner but that the nitrogen atom that is sp2-hybridized is located approximately in a basal position of a square pyramid, while the sp3-hybridized nitrogen atom occupies a position above what is roughly the plane formed by the three methyl carbon atoms and N(1), a result that is consistent with roughly equal abilities of the pi(parallel-to) and pi(perpendicular-to) orbitals in the Cp*WMe3 fragment to form a metal-ligand pi bond. Cp*WMe3(eta2-MeNNMe) decomposes to Cp*WMe3(NMe) in solution in high yield at 60-degrees-C, is not readily reduced by sodium amalgam, is protonated by triflic acid to give [Cp*WMe3(eta2-NMeNHMe)][OTf], and is alkylated by methyl triflate to give [Cp*WMe3(eta2-NMeNMe2)][OTf]. Addition of 1,2-diphenylhydrazine to Cp*WMe3(OTf) in ether did not yield [Cp*WMe3(eta2-NHPhNHPh)][OTf] (1c), but it did yield a mixture of anilinium triflate, [Cp*WMe3(eta2-NPhNHPh)][OTf] (4c), and Cp*WMe3(NPh) over a period of 24 h. Sodium hydride in THF will deprotonate 4c to give Cp*WMe3(eta2-PhNNPh) (5c) in 94% yield. Reduction of 4c by either Na/Hg or cobaltocene led to Cp*WMe3(NPh), 5c, and PhNH2. Although 5C was stable at 65-degrees-C in C6D6 for 4 days, it was reduced by sodium amalgam in C6D6 to give Cp*WMe3(NPh) in ca. 65% yield in 16 h. Addition of methylhydrazine to Cp*WMe3(OTf) gave [Cp*WMe3(eta2-NH2NHMe)][OTf] (1d) quantitatively. Deprotonation of 1d with DBU in THF results in the formation of equal parts of Cp*WMe3(eta1-NNHMe), Cp*WMe3(NH), and methylamine. The reaction between 1d and NEt3 in dichloromethane cleanly generates Cp*WMe3(eta1-NNHMe) in high yield along with dihydrogen. Reduction of 1d in THF yields a mixture of Cp*WMe3(NH), Cp*WMe3(NMe), and Cp*WMe3(eta1-NNHMe). Addition of NH2NMe2 to Cp*WMe3(OTf) in ether at -40-degrees-C yields impure [Cp*WMe3(NH2NMe2)][OTf] (1e). Deprotonation of 1e by either NEt3 or DBU in THF or dichloromethane is proposed to yield Cp*WMe3(NHNMe2) (2e), which then disproportionates to yield a mixture of Cp*WMe3(NH), dimethylamine, and Cp*WMe3(NNMe2). Reduction of 1e with Na/Hg in ether or sodium naphthalenide in THF yields Cp*WMe3(NH) and NHMe2, the expected products of N-N bond cleavage in Cp*WMe3(eta2-NH2NMe2) (3e). Reduction of [Cp*WMe3(eta2-NH2NH2)]+ or Cp*WMe3(eta1-NNH2) in the presence of a proton source yields up to 92% of the possible ammonia, while up to 10 equiv of added hydrazine can be reduced catalytically under similar conditions to yield between 72 and 98% ammonia. It is proposed that the N-N bond is cleaved in Cp*WMe3(eta(x)-NH2NH2) (x = 1 or 2) to give ammonia and Cp*WMe3(NH) in these reductions.